The Emerging Roles and Therapeutic Implications of Epigenetic Modifications in Ovarian Cancer - Wang, Yu; Huang, Zhao; Li, Bowen; Liu, Lin; Huang, Canhua (Frontiers in Endocrinology, 2022)
Ovarian cancer (OC) is one of the most lethal gynecologic malignancies globally. In spite of positive responses to initial therapy, the overall survival rates of OC patients remain poor due to the development of drug resistance and the consequent cancer recurrence. Indeed, intensive studies have been conducted to unravel the molecular mechanisms underlying OC therapeutic resistance. Besides, emerging evidence suggests a crucial role for epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNA regulation, in the drug resistance of OC. These epigenetic modifications contribute to chemoresistance through various mechanisms, including upregulating the expression of MDR proteins, remodeling of the tumor microenvironment, and deregulated immune response. Therefore, an in-depth understanding of the role of epigenetic mechanisms in clinical therapeutic resistance may improve the outcome of OC patients. In this review, we will discuss epigenetic regulation in OC drug resistance and propose the potential clinical implications of epigenetic therapies to prevent or reverse OC drug resistance, which may inspire novel treatment options by targeting resistance mechanisms for drug-resistant OC patients.